Antifungal activity, antibiofilm and synergic effect of diallyl disulfide and diallyl trisulfide against Candida albicans (Research, Society and Development, 2022)
The objective of the present study was to determine the antifungal activity, antibiofilm and synergic effect of the compounds diallyl disulfide and diallyl trisulfide in combination with antifungal agents against clinical isolates of Candida albicans, including also a computational study. Antimicrobial sensitivity tests were performed using the broth microdilution method to determine the minimum inhibitory concentration against C. albicans strains and modulatory activity using the checkerboard technique. The biofilm formation was evaluated by biomass quantification using the violet crystal staining method. For the study of molecular docking computer simulations. The constituents showed relevant antifungal activity against strains of C. albicans. In the modulatory activity assay, demonstrated a synergistic interaction with fluconazole and amphotericin B, with an increase in its antifungal action. The diallyl disulfide, diallyl trisulfide and fluconazole ligands formed complexes with ALS3 enzyme. Then, both compounds were considered promising products for the development of new drugs to prevent candidiasis.